Tax Compliance Costs and the use of e-filing by SMMEs : Tax Compliance Costs and the use of e-filing by SMMEs - Nomlala, Bomi; Oluka, Alexander (The Journal of Accounting and Management, 2021)
This study investigated the costs associated with tax compliance for the small business taxpayer and the factors that motivate them to use the e-filing tax system in Ugu district municipality. The study employed a qualitative research method where semi-structured face-to-face interviews were used as a data collection technique. The purposive sampling strategy was used because the research specifically targeted candidates who are owners of small business. The sample size comprised ten candidates and a thematic analysis was deemed a suitable data analysis method. The findings of the study revealed that the tax compliance costs incurred by taxpayers were mainly monetary cost (practitioners’ fees, lawyers’ fees and cost of travelling to the tax office) and time costs (time spent travelling to the tax office, waiting in the queue to be served and preparing documents for tax submission). In addition, taxpayers pointed out that ease of use of e-filing and demographic factors such as access to the internet and end-user computer knowledge are factors that influence the use of the e-filing tax system. The findings of the study will be of value for the South African revenue services (SARS) and small businesses to become aware of the costs associated with tax compliance and educate them on the necessity of complying with tax law. The research recommends that SARS provide sub-stations or mobile units for rural taxpayers to access the e-filing system and provide the necessary training to the public.